2022
DOI: 10.3389/fcimb.2021.771483
|View full text |Cite
|
Sign up to set email alerts
|

The Qingchangligan Formula Alleviates Acute Liver Failure by Regulating Galactose Metabolism and Gut Microbiota

Abstract: The Qingchangligan formula (QCLGF) is a traditional Chinese medicine that has significant clinical potential for patients with acute liver failure (ALF). However, the experimental evidence of the effect of QCLGF on ALF and the associated mechanisms remain elusive. We aimed to evaluate the function of QCLGF in ALF and the underlying mechanism. ALF was induced in rats by intraperitoneal injection of D-GalN (1100 mg/kg). The Qingchangligan formula was administered to the rats (6.725 g/kg · d) for 5 days, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Due to its chemical properties that allow for transmembrane diffusion, galactose is clinically used to generate glycoconjugates for improved drug absorption, as successfully demonstrated in supplementing dopamine for Parkinson’s patients [ 28 ]. Regulating galactose metabolism has been shown to alleviate acute liver damage and improve some complications of endotoxemia [ 29 , 30 ]. Earlier studies indicated that fatty acid and sugar metabolites are more abundant in phl, suggesting that PLP might regulate metabolic pathways through phl, thus exerting hepatoprotective and menstrual regulation effects.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its chemical properties that allow for transmembrane diffusion, galactose is clinically used to generate glycoconjugates for improved drug absorption, as successfully demonstrated in supplementing dopamine for Parkinson’s patients [ 28 ]. Regulating galactose metabolism has been shown to alleviate acute liver damage and improve some complications of endotoxemia [ 29 , 30 ]. Earlier studies indicated that fatty acid and sugar metabolites are more abundant in phl, suggesting that PLP might regulate metabolic pathways through phl, thus exerting hepatoprotective and menstrual regulation effects.…”
Section: Resultsmentioning
confidence: 99%
“…Lachnospiraceae UCG-008 is considered a potential harmful genus in human colonic microbiota (Huang et al, 2019). Some medicines improve gut microbial dysbiosis by increasing beneficial bacteria and decreasing harmful bacteria, including Lachnospiraceae UCG-008 in order to relieve diseases (Huang et al, 2019;Yin et al, 2021). In conclusion, how gut microbiota influence the development of PCa by disturbing the metabolism is still unclear; further studies are needed to clarify the specific biological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Specific TCM treatments have been shown to reduce potential pathogens, increase SCFA-producing bacteria, and improve gastrointestinal symptoms and the intestinal barrier. In mouse models, these include a combination of curcumin, aloe vera, slippery elm, guar gum, pectin, peppermint oil, and glutamine [429]; a gegen qinlian decoction [430]; a diallyl disulphide garlic extract [431]; a Pi-Dan-Jian-Qing decoction [432]; Qingchangligan [433]; a Buyang Huanwu decoction [434]; Schisantherin A [435]; Chimonanthus nitens Oliv. leaf [436]; Lycium barbarum glycopeptide [437]; a Banxia Xiexin decoction [438]; and a Qing-Fei-Pai-Du decoction [439].…”
Section: Traditional Chinese Medicine and Herbal Therapymentioning
confidence: 99%